The Peruvian Imaginary during the Pandemic: Some interest and observation research lines - De la Cruz Villanueva, Carlos (2021)
The following essay is aimed at promoting two research paths. The first one aims at pointing out possible research pathways in the field of the history of the imaginary. Then various expressions that contribute to understand deeply the Peruvian society in our present can be observed. The second path proposes to observe some of the various daily manifestations that our society has been able to develop in the period of the COVID-19 pandemic. Likewise, this brief essay will point out some new resources, that show some social expressions. They are in constant restructuration and in the process of interaction they develop several manifestations. These resources such as: platforms and social networks are a challenge to research, due to the great amount of information, their constant change, and the social feedback. They should not be ignored in the intellectual field, neither because they are not yet considered as valid resources, nor because the scientific community is not yet prepared for the validation of these resources. They reveal contents that express part of the social dynamics throughout time.